THEORY OF JOURNALISM BY JUOZAS KELIUOTIS FROM THE PERSPECTIVE OF HENRI BERGSON’S PHILOSOPHY - GUDAUSKAS, ANDRIUS (Knygotyra, 2013)
At the start of the 20th century, journalism (perceived as public oral and verbal expression, aimed at the public at large and relying on publishing institutions of newspapers and journals or the first broadcasters of radio shows) as a new professional activity was not yet defined from a scientific point of view in Lithuania. The network of journalism and media was created by those who had a talent and ability to develop this particular sphere. Among the practitioners of journalistic expression in Lithuania was Juozas Keliuotis (1902–1983), publisher and editor-in-chief of the journal “Naujoji Romuva”. Alongside intensive editorial activities he was the first to start developing a theoretical basis for journalism in Lithuania, thus standing out from the other publishers. The founders of communication and information sciences at the start of the 20th century, J. Keliuotis among them, had to face the following challenge: could journalism be clad in scientific clothes? J. Keliuotis’ way of addressing this challenge was formulating theoretical fundamentals of journalism. Being a practitioner, he basically took the standpoint, which clearly declared an attitude towards the theory and practice of journalism as an interdisciplinary field of science. This resulted in the theory of journalism developed by J. Keliuotis. The article aims at presenting the theoretical grounds, which served as a reference point for J. Keliuotis, the founder of the theory of journalism first recorded in Lithuania. The theoretical work of this thinker and publicist is analysed from the perspective of philosophical theory developed by Henry Bergson (1859–1941). The article presents sufficient proof that the theoretical model developed by J. Keliuotis must have been influenced by H. Bergson’s philosophy. In order to reveal it, the text “Lectures on Journalism“ by J. Keliuotis is brought to the fore. This text, published in 2000, takes us back to the very origins of the formation of the theory of journalism and media. Thus, the article analyses the first theory of journalism and media created in Lithuania in the 1920’s and 1930’s. This theory was not destined to grow and develop in the usual academic and publishing sense after World War II. Due to historical-political circumstances the intellectual thought developed by J. Keliuotis was eliminated from public discourse. However, the ideas embodied in J. Keliuotis’ democratic journalistic worldview found echoes in the national consciousness, characterised by resistance manifestations. The echo of these thoughts and the reviving academic tradition can be traced to this day – the current majors in journalism start their Bachelor’s studies at Vilnius university namely with the definition of the mission and functions of journalism as described by J. Keliuotis. The following conclusion is drawn in the article: J.Keliuotis elaborated his theory of ‚journalism making consistent and methodological references to H. Bergson’s philosophy and modeling materialism with the spiritual sphere. He was convinced that the spiritual plane is a source of inspiration and aspirations. J. Keliuotis claimed that any materialism and pragmatic calculations in journalism-related activities such as ideological manifestations, surrender to the appeal of business and diplomatic rhetoric – all this, according to J. Keliuotis, merely distracts from the pursuit of truth, which a journalist is constantly looking for. However, a journalist is neither a fanatic nor a clerical, he needs to have a sense of proportion. The fundamental and final purpose of journalism is a pursuit of and search for true eternal values. Thus, J. Keliuotis saw the correlation between concreteness (practice, experience and experiment) with the whole metaphysical world. He cherished ambitions and aspirations to develop the great theory of Lithuanian journalism and media. Within the context of the respective historical period J. Keliuotis did accomplish this task.